A aprendizagem significativa de sociologia a partir de metodologias ativas - Torres, Ana Carolina Silva (2020)
Sociology, more than a discipline that makes up the High School Curriculum, is a necessary instrument to understand our multifaceted society: its teaching must be seen as a search for the emancipation of individuals, from the formation of their critical sense, denaturalizing the social phenomena and transforming their reality. The present study is a pedagogical intervention that investigated the teachinglearning process of the discipline of Sociology in high school at a school in Juazeiro do Norte, Brazil. We sought to better understand sociology teaching methodologies that facilitate, prioritize or collaborate for meaningful learning. It reflects on the realization of active methodologies of classes, among them the “Wheel of Sociological Conversation” and “Inverted Classroom”. The first comprises generating a more dialogical environment in the class without neglecting important issues in the knowledge of Social Sciences, and the last consists of “inverting” the learning process, making students research and study before classes, reaching they already have the necessary information, being the moment of the meeting destined to clear doubts and accompany the learning. Both consist of making the student more active in their learning process. The methodology used for this pedagogical intervention was action research, which consists of producing knowledge for a more effective use, promoting self-reflection and transformation about the pedagogical practices developed at school. The Conversation Wheel developed as a differentiated Sociology class methodology proved to be a privileged locus of listening, dialogue and broad attention to the contents discussed: the students' participation took place more effectively than in the traditional class, especially with regard to development argumentation and questioning, providing meaningful learning. The inverted classroom, despite all its challenges of restructuring the learning spaces, allowed for greater personalization of teaching, expanding my knowledge about the individual needs of students. Finally, what brought the operationalization of these two active methodologies together was the use of sociological research as a facilitating apparatus for bringing students closer to the concepts, language, and methods of Sociology.